2021
DOI: 10.3390/cancers13133103
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CT to Differentiate Pancreatic Parenchymal Metastasis from Pancreatic Ductal Adenocarcinoma

Abstract: Purpose: To report the computed tomography (CT) features of pancreatic parenchymal metastasis (PPM) and identify CT features that may help discriminate between PPM and pancreatic ductal adenocarcinoma (PDAC). Materials and methods: Thirty-four patients (24 men, 12 women; mean age, 63.3 ± 10.2 [SD] years) with CT and histopathologically proven PPM were analyzed by two independent readers and compared to 34 patients with PDAC. Diagnosis performances of each variable for the diagnosis of PPM against PDAC were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 42 publications
4
8
0
Order By: Relevance
“…Multivariate logistic regression analyses were performed to obtain six radiological features for PM-SCLC diagnosis in CT imaging model or combined model ( Tables 4 , 5 ). The six radiological features were all independent risk factors, including pancreatic duct dilatation, pushed pancreatic duct, tumor size, parenchymal atrophy, vascular involvement and enhancement type, which were similar to those reported in previous studies ( 18 , 26 , 41 ). Although pancreatic duct dilatation wasn’t obtained into the combined model, both Galia, et al.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Multivariate logistic regression analyses were performed to obtain six radiological features for PM-SCLC diagnosis in CT imaging model or combined model ( Tables 4 , 5 ). The six radiological features were all independent risk factors, including pancreatic duct dilatation, pushed pancreatic duct, tumor size, parenchymal atrophy, vascular involvement and enhancement type, which were similar to those reported in previous studies ( 18 , 26 , 41 ). Although pancreatic duct dilatation wasn’t obtained into the combined model, both Galia, et al.…”
Section: Discussionsupporting
confidence: 88%
“…( 18 ) and Barat, et al. ( 26 ) confirmed that absence of pancreatic duct dilatation were the discriminating features for the diagnosis of PM-SCLC against PDAC. In our analysis, pushed pancreatic duct was another independent predictor not obtained into the combined model and not reported in previous studies, but presence of pushed pancreatic duct accounted for 35.5% (33/93) of PM-SCLC and 0.4% (1/206) of PDCA in our datasets.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations